Correction to: Digital technology and practices for school improvement: innovative digital school model - Liisa Ilomäki; Minna Lakkala (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
In the original publication of this article (Ilomäki & Lakkala, 2018) the appendix Table 9 in PDF is in wrong place due to typeset mistake, which should be at the end of the manuscript. The original PDF version has been corrected.